Implementation of a Reliability-Centered Maintenance Plan to Improve the Availability of a Textile Company’s Overlock Machine - Uribe, Sophia Cristina (2020)
DOI: https://doi.org/10.26439/ing.ind2020.n038.4812 This research aimed to implement a reliability-centered maintenance plan to improve the availability of a textile company’s overlock machine with long corrective maintenance downtime during a workday. A maintenance program was developed using a criticality analysis. Then, a failure mode and effects analysis was conducted to analyze the machine’s condition and choose the appropriate actions to be carried out. This process allowed to significantly improve the overlock machine’s availability.